'But It's Your Job To Be Friendly': Employees Coping With and Contesting Sexual Harassment from Customers in the Service Sector. Issue 5 (15th January 2016) - Good, Laura; Cooper, Rae
Abstract : This article analyses how employees in the service sector respond to sexual harassment from customers and attempts to explain why this is so. There are only a small number of previous studies examining the issue of customer‐perpetrated sexual harassment. Those that have been conducted have detailed the nature and prevalence of sexual harassment from customers, but this research lags behind employee experience and some emerging policy responses to this issue. The extant literature, whilst growing, remains largely limited to documenting the phenomenon. In this article, we attempt to create a deeper analysis of customer‐perpetrated harassment by conducting a new review of the literature to develop propositions about how employees respond to it and the factors that influence their responses. These propositions are analysed in relation to a qualitative pilot study with 15 interviewees who had experienced sexual harassment from customers to understand how they reacted and why. The article shows how the social norms and precarious working conditions of the service sector constrain employees from seeking formal redress, leading to the enactment of informal coping strategies and temporary contestations of the situation. This research is important for building our understanding of the influence of workplace context for framing employee responses to customer sexual harassment.